The location of schools in urban area : some planning implications - Abdul Aziz, Norsiah; Agus, Mohd Razali (Fakulti Alam Bina, UTM, 1998)
Education is one of the major contributing factors for producing literate and productive society. The main aim of the Malaysian education policies formulated in 1950's was to integrate the multiracial society. Various programmes and strategies were implemented soas to upgrade the education systems and facilities. Educational policies were consistently reviewed and formulated in line with the national aspirations at that time. The recent one is the Philosophy ofNational Educationformulated in '1990 which aims at producing literate, knowledgeable and civil society so as to meet the future challenges of the 21st century. From time to time, educational development is progressing towards achieving the target. These include not only the curriculum, staffing and budgeting but also the school's built environment i.e. school building and the learning environment. The Ministry ofEducation reported that schools in urban areas such as in Kuala Lumpur, lpoh and Johor Bahru are overpopulated with the average classroom/pupil ratio of 1 : 42. These schools can ,no longer accommodate the increasing number of enrolment as there are limited space for expansion. Hotels, shopping and office complexes are encroaching every inch of urban areas into the surrounding area of the school. The noise and air pollution from the urban activities and traffic congestion are becoming critical and hazardous to school children. As such, the Ministry is concerned with implementing strategies as solutions to the above issues. Basically, the paper will focus on three main topics i,e, the criteriafor school planning in Malaysia, urban issues associated with school location and the current strategies to school planning.